Case report: A creatine kinase-borg scale values-based approach to tailor physical training in a central core myopathy patient - Crisafulli, Oscar; Lacetera, Jessica; Bottoni, Giorgio; Berardinelli, Angela; Grattarola, Luca; Veltroni, Martina; Acquadro, Stefano; Negro, Massimo; Lavaselli, Emanuela; D’Antona, Giuseppe (Frontiers in Physiology, 2024)
Background: Patients with central core myopathy (CCM) can be at risk of exercise-induced rhabdomyolysis and myalgia. Despite its possible positive effects, physical training has been long avoided in these patients as no population-specific exercise adaption strategies have been developed. Here we present the case of a 17-yearold male CCM patient who underwent a 3-month training program tailored to a preliminary test aimed at assessing his physical exertion tolerance measured via changes in serum creatine kinase (CK). The preliminary tolerance test consisted of three 25-minutes sessions (one session per week) of physical exercise (aerobic,resistance and mixed) at an intensity quantified as level 6 of the Borg Category Ratio (CR) 0-10 scale. A blood sample to assess CK was conducted 36 hours following each session. The intervention consisted of a training program (three sessions per week) including both resistance and aerobic exercises concomitant with a personalized nutritional plan. Before and after intervention, a battery of metabolic (indirect calorimetry,bioimpedance) and cardiopulmonary (CPET) tests were performed. Results: After training, improvements of the anaerobic threshold (+6.9%), normalized VO2 max (+15%) and body composition (muscle mass, +1.1 kg;fat mass, -1.1 kg) were observed without pain, rhabdomyolysis, and blood CK augmentation compared to pretraining values. Conclusions: Our results highlight that a mixed aerobic/resistance training, properly tailored and supported by a specific nutritional plan, may safely improve the physical fitness and body composition in a CCM patient. Dosing exercise-induced CK serum change following Borg CR-10 intensity assessment, may be useful to correctly tailor physical exercise in these patients.